Limitations of Online Information on Abdominal Aortic Aneurysm - Carolyn G. Goldberg; Loren Berman; Richard J. Gusberg (International Journal of Vascular Medicine)
Background. Patients with AAA face a complex decision, and knowledge of the risks and benefits of each treatment option is essential to informed decision-making. Here we assess the current information on the internet accessible to patients regarding the management of AAA. Study Design. We performed a search on Google using the keywords “abdominal aortic aneurysm” and reviewed the top 50 web sites. We focused on information related to treatment options and alternatives to treatment and the risks of each option. Results. Twenty-seven websites were included in the study. Nearly 30% of websites discussed the risk of mortality and myocardial infarction after open surgery, compared to only 7.4% for both risks after EVAR. Other complications were listed by fewer websites. Fifty-five percent of websites reported that patients had a faster recovery following EVAR, but only 18.5% mentioned the risk of reintervention after EVAR or the need for long-term surveillance with CT scans. Conclusions. While most websites included descriptive information on AAA and mentioned the potential treatment options available to patients, the discussion of the risks of open surgery and EVAR was inadequate. These results suggest that websites frequently accessed by patients lack important information regarding surgical risk.